Trends and trajectories in “Global South” research: a comparative study of CNKI and WOS database publications - Jiangwei, Liu; Daud, Sity (Frontiers in Political Science, 2025)
ObjectivesThis study analyzes the development of research on the “Global South” through bibliometric analysis with CiteSpace software, drawing on literature from both Chinese scholars using the CNKI database and international scholars from the Web of Science (WOS) database.MethodsThe study employs bibliometric analysis with CiteSpace software and content analysis to compare the research focuses, perspectives, and ideas on the “Global South” between Chinese and international scholars.ResultsThe study finds that both Chinese and international scholars view the “Global South” as a complex and evolving concept. However, Chinese scholars focus on understanding and applying the concept in the context of China’s evolving role in international politics, while international scholars explore the concept across various fields through case studies.ConclusionThe study calls for an integrated interdisciplinary discussion combining political science, economics, sociology, and cultural studies to better understand the complexity and diversity of the “Global South.” It also highlights the importance of academic collaboration between Chinese and international scholars to achieve a global consensus and suggests expanding case studies for policy implementation.